PERADABAN ISLAM DI NUSANTARA MASA PENJAJAHAN DAN PERKEMBANGAN PENDIDIKANNYA - Novi Artika; Dwi Setyanita; Anang Sholikhuddin (CV. BAROKAH PUBLISHER, 2026)
This research aims to analyze the dynamics of Islamic civilization in the Indonesian Archipelago (Nusantara) during the colonial era and how Islamic education evolved as a response to colonialism. Using a qualitative historical method, the study finds that while colonialism disrupted Islamic political structures, it simultaneously triggered intellectual resistance. Islamic education transformed from traditional 'pesantren' into modern 'madrasahs' and schools, which served as strongholds for cultural identity and independence movements. The study concludes that the resilience of Islamic civilization in Nusantara was rooted in its educational adaptability and the pivotal role of ulama and Islamic organizations.